Distinctive Roles of 5-aza-2′-deoxycytidine in Anterior Agranular Insular and Basolateral Amygdala in Reconsolidation of Aversive Memory Associated with Morphine in Rats - Liu, Peng; Zhang, JianJun; Li, Ming; Sui, Nan (Frontiers in Behavioral Neuroscience, 2016)
5-aza-2-deoxycytidine (5-aza), an inhibitor of DNA methyltransferases (DNMTs), has been implicated in aversive memory and the function of brain region which processing affect. However, little is known about the role of 5-aza in the reconsolidation of opiate withdrawal memory. In the present study, using the morphine-naloxone induced conditioned place aversion (CPA) model in rats, we injected 5-aza into agranular insular (AI), granular insular (GI), basolateral amygdala (BLA) and central amygdala (CeA) immediately after the memory retrieval and tested the behavioral consequences at 24hours, 7 days and 14days after retrieval test. We found that 5-aza injection into AI disrupted the reconsolidation of morphine-associated withdrawal memory, but 5-aza injection into GI had no impact on the reconsolidation. Meanwhile, 5-aza injection into BLA but not CeA attenuated the withdrawal memory trace 14 days later. However, 5-aza administration to rats, in the absence of memory reactivation, had no effect on morphine-associated withdrawal memory. These findings suggest that 5-aza interfere with the reconsolidation of opiate withdrawal memory, and the roles of insular and amygdala in reconsolidation are distinctive.